Robotnicze środowiska pisarskie na Ziemi Lubuskiej w latach 1976-2015 = The Lubusz Region workers' writing community in the period of 1976-2015 - Rudiak, Robert (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
The The development of a culture co-created by the working class continued throughout the People`s Republic of Poland. Thus, already in 1950, a group of working-class writers had formed in Warsaw, called "We`re building" - producing, in the spirit of socialist realism, typical socialistic novels glorifying work, and these were published in the press. In 1962, the Workers` Writing Club (KRP) was established in Warsaw, and in 1976 another such club was initiated in Gorzów Wielkopolski, operating in the largest factory in the town, ZWCh "Chemitex-Stilon". The working-class artists published their texts in magazines published by the industrial firms "Stilon Gorzowski" and "Gorzowska przemysłówka". In 1980, KRP in Warsaw was transformed into a nationwide cultural movement called the Workers` Association of Cultural Creators (RSTK), and one of its first regional branches was in Gorzów, founded on the basis of the previously functioning Workers` Writing Club. As the movement gained momentum across the country, a branch was established in Zielona Góra in as early as 1986, comprising artists and cultural activists at the Zastal factory. Workers engaged in writing were published in the magazine "Zastalowiec", and presented on the factory`s own radio station, and, eventually, numerous anthologies of poetry were published and occasional competitions organized. By the end of the 1980s, forty-six branches of the Association existed in Poland. However, at the end of the 1990s the Zielona Góra sections of RSTK ended their activities in response to the liquidation of a number of industrial factories.
Keywords: kluby literackie; literaci; pisarze polscy; robotnicy; Robotnicze Stowarzyszenie Twórców Kultury; środowisko literackie; Gorzów Wielkopolski; Zielona Góra; literary clubs; Polish writers; writers; workers; literary community